Doorframe carved with the figures of river Goddess and dvaralapalas (door guardians) - Temples of India Project Team (Jio Institute, 2024)
The garbhagriha (sanctum sanctorum) can be accessed through a doorframe which is carved with the figures of river Goddess and dvaralapalas (door guardians) at the bottom and the trinity—Shiva, Vishnu and Brahma on the lintel. The dvarashakas (architraves or doorjambs) are plain except for one, which shows a floral design.